Tests of applications of transfer films in seams lamination technology - Halina Szafrańska; Ryszard Korycki (Journal of Natural Fibers, 2019)
The main goal of the article is to investigate the replacibility of sewn stitches by laminated seams in cotton clothing products. The research objects are seams prepared experimentally in industrial conditions, laminated with thermal transfer film in the form of tape. There are determined (i) the lamination parameters on thermal press influencing the quality index of created seams, (ii) the effect of laminated seams on the aesthetic properties of the product. The permissible values of the quality index are compared for laminated and sewn seams. Hence, we conclude that the selected sewn seams can be replaced by laminated structures.